AN EXAMINATION OF GOVERNANCE AND SECURITY IN KADUNA STATE SINCE 1999 - SABO Anche Ugah; Sunday Vincent Akwashiki; Aminu Davidson Bowo (International Studies Journal)
Kaduna State is a heterogenous society with over forty (40) ethnic groups, hence; making it a peculiar State with a lot of security challenges thereby making governance a task. This paper seeks to examine governance and security in Kaduna State, it also discusses the security challenges and the State of governance in Kaduna State. The study adoptsboth primary and secondary sources in the documentation of the outcome of the research work. Primary sources were strictly on interviews conducted while the written sources which comprises of; documents such as; monographs, manuscripts, textbooks, journals, magazines, and otherswere examined, documented, and well-acknowledged. The study helps in the understanding of the State and its dichotomous nature, what governance and security are, and whatconstitutes security challenges in Kaduna State. This research work is coming at a time when governance and security are challenging, hence; it will help the policymakers understand the peculiarity of security challenges in the state and thus; help make policies that will enhance the security of her citizens by providing good governance to the people. The study will help the government to enlighten her citizens on the importance of education, tolerance, true dialogue, and reconciliation among others to serve as tools with which to douse the security challengesfaced by the state which will ensure the peaceful co[1]existence of members of the different religion’s groups and ethics,and thereby promotes harmonious living, restoration of peace, security, growth, and stability, and order in the State.